Association of Palb2 variants with risk to breast cancer and molecular characterisation of PALB2 tumours / Ng Pei Sze - Ng, Pei Sze (2021)
Purpose: Germline rare protein truncating variants (PTVs) in PALB2 are associated with an increased risk to breast cancer. At present, most of the available data on genetic predisposition to breast cancer are derived from studies in women of European descent, and it is unclear the extent to which population-specific differences in genetic and lifestyle factors may contribute to differences in lifetime risk to breast cancer in women of other ancestries. This study sought to determine the prevalence of, mutation spectrum in and the risk estimates associated with PALB2 in a multiethnic cohort of 7840 breast cancer cases and 7928 healthy individuals from Malaysia and Singapore. In addition, this study sought to describe the pathological and molecular characteristics associated with cancers arising in carriers of PTV of PALB2. Methods: Mutation testing was performed on genomic DNA from peripheral blood using targeted panel sequencing of 35 known or suspected breast cancer susceptibility genes. Library preparation was conducted using the Fluidigm Access Array or Fluidigm Juno system and the final pooled products were sequenced on the Illumina Hiseq platform. Sanger sequencing was conducted to confirm all variants identified in the bioinformatics analysis. For somatic mutational analyses, DNA from fresh frozen tumour sections and matched normal DNA from peripheral blood were subjected for whole exome sequencing (WES). For tumour gene expression analyses, RNA from fresh frozen tumour sections were analysed using whole transcriptomic RNA sequencing (RNA-seq). Results: The case-control analysis revealed that germline PTV in PALB2 were rare but associated with significant increased risk of breast cancer [OR=5.18, 95% CI 2.71 to 9.90, p<0.0001]. However, rare missense variants in PALB2 [when analyzed as a group] were not associated with increased risk of breast cancer. We found that tumours with PTV in PALB2 have characteristics that were iv similar to BRCA1 and BRCA2 tumours, having significantly more somatic alterations, and a high proportion of mutational signature and genomic scar scores characteristic of deficiencies in homologous recombination (HR), compared to tumours arising in patients with no alterations. In addition, we report that unlike BRCA1 and BRCA2 tumours, PALB2 tumours did not have high prevalence of TP53 somatic alterations or an enriched immune microenvironment. Conclusion: In this multi-ethnic cohort, which is unselected based on age or family history, germline PTVs were identified in 0.73% of breast cancer cases and 0.14% healthy individuals. Based on the molecular profiling of PALB2 tumours, the findings from this study suggest that breast cancer patients with PALB2 PTVs have similar molecular characteristics to BRCA1 and BRCA2 tumours and are therefore likely to benefit from the emerging targeted therapies for BRCA carriers such as platinum-based chemotherapy and/or PARP inhibitors. These results confirm that PALB2 is the most clinically significant breast cancer susceptibility gene after BRCA1 and BRCA2, thus justifying the inclusion of PALB2 into the mainstream genetic testing to improve the management of cancer risk for affected and unaffected carriers. Key words: PALB2, breast cancer, germline, tumour genomics, transcriptomics